GAMBARAN KEPATUHAN MENGGUNAKAN ALAT PELINDUNG DIRI (APD) PERAWAT GUNA MENCEGAH INFEKSI NOSOKOMIAL DI BALAI BESAR KESEHATAN PARU KOTA MAKASSAR - Andi Nailah Amirullah; Mudrika; Salki Sasmita (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Personal protective eqiutment (PPE) is a set of safety equitmen used by workers to protect all or part of its body from the possibility of exposure to potential hazards in the work environtment agains aoccupational accidents and disease. Nurse are required to use personal protetive aquipment to reduce accopational safety and health risks in hospitals in providing nursing action. The purpose of this study was to know the description of knowledge of attitude and actions on the nurse with using personal protective aquitment in terms to prevent nosocomial infection in Central Pulmonary Health Makassar City. This research was conducted at Central Pulmonary Healt Makassar which an descrptif analytical research. The number of samples was 52 respondents who worked at inpatient care room. The sampling technique was made by total sampling technique. The results of the study demonstrating statistic test result obedience the nurse to use PPE show suficient results is 30 peopel (80,3%) and less 22 peopel (19,7 %). Knowledge of nurse using PPE, enough is 14 people (19,4%) and less 38 peopel (80,6%). Based on attitude, which is enough 19 people (29,1%) and less 33 peope (70,9%). Based on action, enough as much 38 people (78,3%) and less 14 people (21,7%) at Balai Besar Kesehatan Paru Kota Makassarin inpatient care room at Central Pulmonary Health Makassar. From the results of this study is expected to perform various activities and improving the quality of human resources, especially nurses to better understand the PPE, and in addition to knowing and understanding well carry out and properly use the Personal Protective Equipment in order to avoid all threats of danger.